Immunomodulation with minocycline rescues retinal degeneration in juvenile neuronal ceroid lipofuscinosis mice highly susceptible to light damage - Katharina Dannhausen; Christoph Möhle; Thomas Langmann (The Company of Biologists, 2018)
Juvenile neuronal ceroid lipofuscinosis (jNCL) is a rare but fatal inherited lysosomal storage disorder mainly affecting children. The disease is caused by mutations in the CLN3 gene that lead to the accumulation of storage material in many tissues, prominent immune responses and neuronal degeneration. One of the first symptoms is vision loss followed by motor dysfunction and mental decline. The established Cln3Δex7/8 mouse model mimics many pathological features of the human disease except the retinal phenotype, which is very mild and occurs only very late in these mice. Here, we first carefully analyzed the retinal structure and microglia responses in these animals. While prominent autofluorescent spots were present in the fundus, only a moderate reduction of retinal thickness and no prominent microgliosis was seen in young CLN3-deficient mice. We next genetically introduced a light-sensitive RPE65 variant and established a light-damage paradigm that showed a high susceptibility of young Cln3Δex7/8 mice after exposure to 10,000 lux bright light for 30 min. Under these 'low light' conditions, CLN3-deficient mice showed a strong retinal degeneration, microglial activation, deposition of autofluorescent material and transcriptomic changes compared to wild-type animals. Finally, we treated the light-exposed Cln3Δex7/8 animals with the immunomodulatory compound minocycline, and thereby rescued the retinal phenotype and diminished microgliosis. Our findings indicate that exposure to specific light conditions accelerates CLN3-dependent retinal degeneration, and that immunomodulation by minocycline could be a possible treatment option to delay vision loss in jNCL patients. This article has an associated First Person interview with the first author of the paper.